Direct anterior versus posterolateral approach for bipolar hip hemiarthroplasty in femoral neck fractures: a prospective randomised study. Issue 6 (November 2020) - Verzellotti, Simone; Candrian, Christian; Molina, Mauro; Filardo, Giuseppe; Alberio, Riccardo; Grassi, Federico A
Introduction: Femoral neck fractures are a major problem in orthopaedic practice, having a huge impact on society, and involving a large number of elderly patients for whom early recovery is paramount. Thus, the aim of this study was to compare 2 surgical approaches, direct anterior (DA group) versus posterolateral (PL group), used for bipolar hip hemiarthroplasty (BHA) with femoral neck fractures in order to assess pain recovery after surgery. Our hypothesis was that early pain recovery would be faster in the DA group. Methods: 100 patients were randomised to surgery using either a DA group or PL group approach, and were then followed up for 6 months. Surgical time, intra- and postoperative complications were recorded for each patient. The main outcome, pain, was recorded using an NRS scale at 3 days, 1, 3 and 6 months after surgery. At the same time, patient status was evaluated using Activities of Daily Living and Cumulated Ambulation Score scales. Results: Surgical time was longer in the DA group ( p   <  0.0001). Pain perception at 3 days and at 1 month after surgery was significantly lower in DA group patients ( p   <  0.0001). The results of the other scales were comparable in the 2 groups (at 3 days, 1 and 3 months after surgery). Discussion: The DA approach offers a significant advantage in terms of pain perception up to 1 month after the operation. Early recovery in terms of pain perception is an important finding. Future studies should explore whether this early pain reduction could translate into a faster rehabilitation programme for an earlier recovery of full function. Clinical trial registration: Protocol 423/CE; Study n. CE 41/15.